ANALISIS PENERAPAN E-GOVERNMENT DALAM LAYANAN PENDANAAN RISET: STUDI PADA PLATFORM eRISPRO LPDP - Putri, Fitrianindita Rahayu; Putra, Fahdiansyah; Rahman, Abdul (Jurnal Progress Administrasi Publik, 2025)
This study aims to analyze the implementation of e-government in research funding services through the eRISPRO platform developed by Lembaga Pengelola Dana Pendidikan (LPDP), especially by assessing aspects of efficiency, transparency, accountability, accessibility, and inclusiveness in managing research grants. This system is designed as an integrated digital service to manage the grant process, from proposal submission to selection, disbursement, and reporting. The study uses a qualitative descriptive approach, gathering data by directly observing the eRISPRO system and conducting semi-structured interviews with LPDP staff involved in managing the program. The results of the study show that eRISPRO has increased the efficiency of grant administration through process digitization, such as the use of e-Stamps, automatic notifications, and online reporting. In terms of transparency and accountability, this system provides access to reviewer assessment records, activity-based RAB verification, and an achievement dashboard that supports information transparency. However, challenges are still found in the aspects of accessibility and inclusiveness, especially related to the digital literacy gap and the dominance of merit-based approaches that have not fully reached institutions in non-leading areas. This study contributes to the literature on e-government by highlighting digital public service platforms in a research sector that has not been widely studied before and providing recommendations for improvements so that the implementation of such digital services can be more equitable and sustainable. Keywords: Digital Public Service; e-Government; eRISPRO; LPDP; Research Funding